2016
DOI: 10.1080/13557858.2016.1180347
|View full text |Cite
|
Sign up to set email alerts
|

Pathways between under/unemployment and health among racialized immigrant women in Toronto

Abstract: Our study provides needed qualitative evidence on the gendered and racialized dimensions of under/unemployment, and adverse health impacts resulting from this. Drawing on intersectional analysis, we unpack the role that social location plays in creating highly uneven patterns of under/unemployment and negative health pathways for racialized immigrant women. We discuss equity informed strategies to help racialized immigrant women overcome barriers to stable work that match their education and/or experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(124 citation statements)
references
References 52 publications
4
119
0
1
Order By: Relevance
“…Our study contributes to the small body of empirical research that has addressed the relationship between precarious employment and geographical mobility (Bohle et al, 2004;Zeitinoglu et al, 2004;MacDonald, 2009;Access Alliance Multicultural Health, 2011;Wilson et al, 2011;Fitzpatrick and Neis, 2015;Premji and Shakya, 2016), and to the growing number of studies that have looked at how changes in the nature of employment is necessitating increased mobility from workers (Newhook et al, 2011;Haan et al, 2014). To our knowledge, ours is one of only two empirical studies that have specifically focused on the multiple and complex ways in which precarious employment impacts daily commutes (Fitzpatrick and Neis, 2015), and the only one to have done so in an urban context.…”
Section: Discussion and Recommendationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Our study contributes to the small body of empirical research that has addressed the relationship between precarious employment and geographical mobility (Bohle et al, 2004;Zeitinoglu et al, 2004;MacDonald, 2009;Access Alliance Multicultural Health, 2011;Wilson et al, 2011;Fitzpatrick and Neis, 2015;Premji and Shakya, 2016), and to the growing number of studies that have looked at how changes in the nature of employment is necessitating increased mobility from workers (Newhook et al, 2011;Haan et al, 2014). To our knowledge, ours is one of only two empirical studies that have specifically focused on the multiple and complex ways in which precarious employment impacts daily commutes (Fitzpatrick and Neis, 2015), and the only one to have done so in an urban context.…”
Section: Discussion and Recommendationsmentioning
confidence: 86%
“…This research brought to light the pervasiveness of precarious employment and its wide-ranging negative impacts for workers, families and communities (Wilson et al, 2011;Access Alliance Multicultural Health, 2012;Access Alliance Multicultural Health and Community Services, 2012). The study we describe builds on results from this body of research that have pointed to the important role of mobility (Access Alliance Multicultural Health, 2011; Premji and Shakya, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that a lack of effective resettlement services, including employment support, may contribute to increased distress. Research examining the interaction of employment and mental health outcomes with other vulnerable populations, such as low income women who struggle to find childcare in the United States [38], low education individuals in Brazil [39], and racial minorities in Canada [40] also demonstrated that non-professional employment or under employment results in psychological distress. Other scholars posit that refugees resettled for longer periods may experience employment as a barrier due to a concurrent decrease in social program funding [24,34].…”
Section: Discussionmentioning
confidence: 99%
“…19,21,[26][27][28] They can be overqualified 24 and may face language or cultural barriers that make them less likely to seek compensation and medical assistance. 29,30 2 | DISCUSSION…”
Section: Workplace Structural Vulnerabilitiesmentioning
confidence: 99%